Propuesta de estructura corporativa para la Empresa Distribuidora Ochenta y Seis S.A. - Chavarría-Umaña, Beatriz; Villalobos-Ramírez, Alex; Garro-Carvajal, Luis Adolfo (Instituto Tecnológico de Costa Rica, 2017)
Distribuidora Ochenta y Seis S.A was born almost 30 years ago in San Ramón, Alajuela, due to the vision and entrepreneurship of a young bicycle lover who started its business in a garage at early age. During his first steps in the business world, he showed a lot of dedication, honest work and effort which has led his company to be one of the strongest in the western area of Costa Rica and one of the three biggest players in the bicycle Market in which it competes; However due to market evolution and strong competition, the organization begins with a process of professionalization and structuring which had allowed the company to not only survive but also thrive. Part of the story also includes reforming the company´s trident of values (corporate, family and property) into a single path that guarantees the success and healthy coexistence among the parts. That is why we are trying to carry out a project with a main question. Does the company Distribuidora Ochenta y Seis have the necessary corporate governance to supervise, direct, manage and measure the strategic and functional performance of the company, and also the tools to guide the good family business practices, which guarantee their operation and evolution with the passing of generations? The objective of this research is to give an affirmative answer to that question and to be a support for the company and the family business interested in its success.
Proyecto de Graduación (Maestría en Dirección de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2017.
Keywords: Estrategia; Evolución; Organización; Dirección; Gestión de negocios; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies